Associação de polimorfismo no gene FTO com obesidade e sensibilidade à insulina em pacientes ambulatoriais - Campos, Lunara da Rosa (2013)
Obesity is a major risk factor for type 2 diabetes mellitus (T2D), cardiovascular disease (CVD) and metabolic syndrome (MetS). Studies show that genetic factors related to adiposity could influence the risk of T2D. Genome-wide association study (GWAS) has found an association between a variant rs9939609 in intron 1 of the FTO gene (fat mass and obesity associated) and the risk of obesity and insulin sensitivity. Here we evaluated the association SNP rs9939609 FTO gene with T2D and investigated the impact of genetic variation in the FTO gene on measures of obesity, clinical and biochemical predictors of risk of cardiovascular disease. In this case-control study we genotyped 275 non-T2D and T2D subjects followed up at Mato Grosso Federal University Hospital, Brazil. It was observed similar genotype distribution of variant in both individuals non- T2D and T2D, as well as in the presence of MetS. Evaluating the interactions between the rs9939609 genotype we verified that the individuals homozygotes A-allele risk in the absence of disease exhibited lower body mass index (BMI), similar to T2D, when compared with other genotypes of non-T2D. However, individuals T2D homozygotes AA presented higher waist to hip ratio (WHR). Carries the risk allele T2D had lower values of quantitative insulin-sensitivity check index (QUICKI) when compared to other groups and genotype. Individuals AA showed high levels of total cholesterol (CT) and greater ratio triglycerides/HDL-cholesterol, in both groups. Thus, our results suggest that SNP rs9939609 FTO gene could be associated with susceptibility to T2D, in addition to exposing individuals to atherogenic lipid profile, which reveals to be a predictor for the development of cardiovascular disease.